MANAJEMEN PROGRAM FULL DAY SCHOOL DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI MTS NEGERI 2 BREBES - Eti Hadiati; Isqi Nabila Nurfaizah Jannah Jafa (Al-Mahabbah : Jurnal Manajemen Pendidikan Islam, 2025)
The full day school program has emerged as an educational model expected to systematically and structurally foster students’ religious character. This study aims to analyze the management of the full day school program in shaping the religious character of students at MTs Negeri 2 Brebes. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model. The findings reveal that the management includes planning religious activities such as daily Qur’anic recitation (tadarus), dhuha and dhuhur congregational prayers, the Qur’an reading and writing (BTQ) program, istighosah, and the 5S habituation program (smile, greet, salute, polite, courteous). These activities are consistently scheduled and integrated into students’ daily routines. Evaluations are conducted through religious attendance logs, tadarus assessments, and direct supervision by teachers and homeroom advisors. The results indicate that the full day school program significantly contributes to instilling religious values through worship practices and spiritual character development. The conclusion of this study is that well-designed and consistently implemented full day school management serves as an effective strategy in developing students’ religious character, as reflected in their worship behavior, ethical conduct, and discipline both in school and in the community.